Efforts to Improve Service Quality at Skenario Kopi Cafe Based on Consumer Needs Using Quality Function Deployment - Fariza Amalia; Handy Nur Cahya; Dwi Eko Waluyo; Fakhmi Zakaria (Jurnal Indonesia Sosial Sains, 2024)
Faced with fierce competition, coffee shops need to stay in tune with evolving customer preferences. This research was conducted the Quality Function Deployment (QFD) method, specifically the House of Quality (HoQ) tool, to analyze feedback from subject consist of 100 customers of Skenario Kopi Cafe. The HoQ is a structured approach that translates customer desires (Voice of Customer or VoC) into actionable technical improvements. The sampling technique is based on purposive sampling technique. Analysis of Validity Test and Reliability Test data using SPSS 24 software. The research identified 15 key customer needs, categorized by their level of importance. They then compared these needs to 5 potential technical responses that Skenario Kopi Cafe could implement. Based on this analysis, the result showed such as prioritizing communication training for staff, followed by facility upgrades, and lastly, implementing regular performance evaluations. By analyzing the relationships between these factors, the researchers were able to prioritize the actions that would have the greatest impact on customer satisfaction.